AN HISTORICAL LINGUISTICS CORPUS (Centuries XVI-XIX) - Banza, Ana Paula (2013)
The aim of the present paper is to present and discuss a work in progress that involves: the creation of online editions of historical documents of a metalinguistic nature, which function both as publications and corpora, allowing for the comparison of manuscript images with the diplomatic edition and providing tools for analysis; the application and development of tools that can easily be manipulated by users and adapted to different kinds of historical texts.